2014
DOI: 10.1039/c4lc00050a
|View full text |Cite
|
Sign up to set email alerts
|

Make it spin: individual trapping of sperm for analysis and recovery using micro-contact printing

Abstract: In this article, we describe the development of a high throughput platform to spatially manipulate viable sperm for motility measurements and recovery of the best single sperm for fertilization purposes. Micro-contact printing was used to pattern islands of adhesive proteins (fibronectin) separated by sperm repellent species (Pluronic acid F-127) on commercially available polystyrene substrates. Following washing, arrays of viable single sperm were captured onto the islands demonstrating for the first time tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…This effect may be of minor importance in typical mL volume chambers, but will certainly become a dominant issue in the miniaturized micro or nanoliter volume chambers used in microfluidic lab-on-chip devices (platforms all-in-one). 4,5,[20][21][22] In other words, it would be highly desirable to find a way to counteract the material-independent and ubiquitous cell accumulation at the chamber boundaries with a mechanism leading to the formation of a more uniform density distribution of microswimmers.…”
mentioning
confidence: 99%
“…This effect may be of minor importance in typical mL volume chambers, but will certainly become a dominant issue in the miniaturized micro or nanoliter volume chambers used in microfluidic lab-on-chip devices (platforms all-in-one). 4,5,[20][21][22] In other words, it would be highly desirable to find a way to counteract the material-independent and ubiquitous cell accumulation at the chamber boundaries with a mechanism leading to the formation of a more uniform density distribution of microswimmers.…”
mentioning
confidence: 99%
“…In addition to the physical trapping of the cell inside the microtube, the cell‐tube binding is supported by attaching biomolecules on the inner tube surface that interact with the sperm cell membrane during the coupling. There are several candidates that are able to bind to sperm cells such as Fn, hyaluronic acid, and others . The glycoprotein Fn is a component of the extracellular matrix which is also present in the surroundings of the oocyte .…”
Section: Resultsmentioning
confidence: 99%
“…The integrins connect the external environment with the interior cytoskeleton of the cell and act as mediators . Fn was recently utilized in a high throughput platform to attach and analyze single spermatozoa to a planar surface . One of the goals in this work was to attach Fn on the inner tube lining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nascimento et al (18) showed the potential to entrap single sperm cells using laser tweezers and to measure their motility optically. In previous work from our group, we used microcontact printed fibronectin spots to entrap single sperm cells, after which their motility was analyzed using image analysis (19). With a different approach, we used a hydrodynamic trapping procedure to entrap single sperm cells in small microfluidic channels to study their viability, acrosome integrity, and sex chromosome content using fluorescent analysis (20).…”
mentioning
confidence: 99%